See What I Mean? Reading Visual Verbs Modulates Ocular Dynamics - Garcia-Serrano, A (Routledge, 2025)
Embodiment research shows that body movements can be influenced by action verbs. Yet, by analogy, can peripheral perceptual systems be modulated during processing of sensory words? Here we tackle this question by targeting ocular dynamics during reading of visual verbs. In an eye-tracking experiment, participants read sentences word by word, all with the same structure: verb + article + noun + adjective. Half contained visual verbs (e.g. see the ripe cherry); the other half contained non-visual sensory verbs (e.g. smell the pleasant cinnamon). We compared the pupil size as well as the number and duration of fixations for each sentential item between conditions. Relative to the non-visual condition, the visual condition involved reduced pupil dilation on the verbs, nouns, and adjectives, there being no effects on the number and duration of fixations. These findings indicate that ocular dynamics are modulated by sight-related meanings, informing accounts of peripheral language embodiment. © 2025 Informa UK Limited, trading as Taylor & Francis Group.